Exploring MindMend: an innovative mental health support apps for autistic adolescents and their caregivers - Zannat, Nahreen; Mahmud, Murni (UUM Press, 2024)
Teenagers with mild autism spectrum disorders (ASD) and those who care for them face difficulties. Conventional mental health therapies frequently ignore culturally specific factors that are crucial to the patient's overall wellness. The paper aims to introduce and evaluate "MindMend" a smartphone software specifically designed for teenagers with mild autism spectrum disorders (ASD) and their caregivers. It focuses on examining the effectiveness of MindMend in reducing caregiver stress and alleviating autism symptoms. Additionally, it emphasises the significance of providing comprehensive support that considers the cultural and religious nuances of the target population. The software includes modules for social skills training, emotion regulation, and cognitive-behavioural therapy. Users may participate in a helpful online community, track their progress, and set goals. Early research demonstrates encouraging outcomes in reducing caregiver stress and autism symptoms. MindMend seeks to be a flexible instrument that enhances mental health while honouring subtleties related to culture and religion. The methodology integrates software development, evidence-based therapeutic approaches, and outcome evaluation. It aims to create a specialised mental health solution for teenagers with mild autism and their caregivers. The approach strongly emphasises addressing their unique challenges and providing comprehensive support. The development of MindMend involves creating an innovative smartphone application that offers specialised content. The paper assesses how well MindMend helps reduce stress for caregivers and alleviate autism symptoms in teenagers with mild ASD. The evaluation likely includes quantitative and qualitative methods to measure the digital system's impact on users' well-being.